Sintering aid composition

By using slurry phase hydrocracking concentrated residue from heavy oil raw materials as the sintering aid composition, the problem of release of mechanical impurities and volatile compositions in the sintering aid is solved, and the manufacturing and environmental impact of high-strength carbonaceous products are achieved.

CN119528590APending Publication Date: 2025-02-28TAIF JOINT STOCK COMPANY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410422356.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-04-09
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art cannot effectively control the content of mechanical impurities and the release of volatile composition in the sintering aid, resulting in poor mechanical strength of the prepared carbonaceous products, and no attention is paid to the influence of aromatic hydrocarbon content, affecting wetting and mechanical strength.

Method used

The concentrated residue from slurry phase hydrocracking from heavy oil raw materials is used as the sintering aid composition. By controlling the hydrocracking process, the aromatic hydrocarbon content is increased, the carboene and oil coke content is reduced, and the appropriate content of mechanical impurities is ensured.

Benefits of technology

The ability to manufacture high-strength carbonaceous products is achieved, the impact of coal asphalt production on the environment is reduced, the hydrocracking residue of heavy oil raw materials is effectively utilized, and the wetting and mechanical strength of the sintering additives are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528590A_ABST
    Figure CN119528590A_ABST
Patent Text Reader

Abstract

The invention relates to petrochemistry, in particular to a sintering aid composition for manufacturing carbonaceous products for the metallurgical industry. The present invention relates to a sintering aid composition for the manufacture of carbonaceous articles, consisting of concentrated residues from slurry phase hydrocracking of a heavy oil feedstock, having an aromatic hydrocarbon content in the range of 23 wt.% to 27 wt.%, in which the sintering aid composition is characterized in that the total weight loss is 50 wt.% to 51 wt.% in the temperature range of 30 DEG C to 850 DEG C, and in which the total weight loss is 50 wt.% to 51 wt.% in the temperature range of 30 DEG C to 850 DEG C. The weight loss in the temperature range of 290 DEG C to 570 DEG C is about 95 wt.% of the total weight loss. The performance characteristics of the sintering aid are improved to make high strength carbonaceous articles for metallurgical industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sintering aid composition for manufacturing carbonaceous products used in the metallurgical industry. Background Art

[0002] The unsatisfactory state of the raw material substrate for coking, the expected inadequate sintering of this substrate during coal sintering and the increasing environmental protection requirements determine the need to introduce new methods for preparing and carbonizing coal that allow the production of coke of the desired quality with fuels of lower coking power. One of such methods is the introduction of petroleum-derived organic additives into the charge. Sintering aids are solid petroleum residues that are added to the coal charge instead of fat coal.

[0003] During the oil refining process, various heavy residues are produced, such as tar. The heavy residues are then processed to make industrially useful products. However, processing the heavy residues produces a large number of unwanted products that must be utilized. Therefore, there is also a need to beneficially use the products derived from the secondary processes of heavy residue processing.

[0004] It is known in the art that the modifying effect of additives depends on their hydrogen donor properties and aromaticity. The modifying influence of additives is generally explained by their ability to cause deagglomeration, plasticization of coal, or by their possibility of forming liquid crystal bonds at the interfaces of coal particles, the co-carbonization of the latter can produce coke with an optical structure of anisotropic mosaic shape, which strengthens its structure [Polisar, EL "Obzhig koksopekovykh materialov srazlichnym soderzhanien svyazuyushchego" ("Sintering of pitch coke materials with different binder contents") / / "Khimiya tvyordogo topliva", 1976, No. 64, pp. 53-56].

[0005] From the article “Neftaynoy pek dezintegrirovanniy – al'ternativnoe svyazuyushchee dlya anodovnovogo pokoleniya” (“Decomposed petroleum pitch as an alternative binder for next-generation anodes”) by AAUgapyev, OIDoshlov, published in IrGTU Vestnik, issue 6, 2013, it is known that residual oil with high density, aromaticity and low sulfur content is the most ideal raw material for the production of petroleum pitch. However, the resources of low-sulfur residues are very scarce due to the high demand for raw materials of this quality for coking.

[0006] Patent RU2418837 (published on May 20, 2011, int.cl.C01B 57 / 04) discloses the use of asphalt residue from the production process of light fractions of oil products as a sintering aid, wherein the asphalt residue has the following characteristics: ash level A d No more than 2.5%; the output of volatiles V daf not more than 70%; sulfur content not more than 5%; expansion up to 20 mm; Roga index (IR) up to 10. The disadvantage of this solution is that it is impossible to control the content of mechanical impurities in the sintering aid and the amount of volatile components released when the charge is in the plastic state, which may lead to unsatisfactory characteristics of the prepared carbonaceous product, such as mechanical strength. Moreover, this solution does not pay attention to important parameters, such as the content of aromatic hydrocarbons in the sintering aid. Since this parameter affects the wettability of the sintering aid, it helps to improve the mechanical strength of the sintered body. Summary of the invention

[0007] The technical problem solved by the present invention is to provide a sintering aid composition comprising concentrated residue from slurry phase hydrocracking of heavy oil feedstock and having excellent performance characteristics for use as a sintering aid for manufacturing high-strength carbonaceous products for metallurgical industry.

[0008] One of the technical effects of the present invention is to provide a sintering aid composition made from concentrated residues from slurry phase hydrocracking of heavy oil feedstocks, which allows the manufacture of high-strength carbonaceous products for the metallurgical industry.

[0009] Another technical effect of the present invention is to involve a residue from the hydrocracking of a heavy oil residue feedstock in the production of a sintering aid composition for use in the manufacture of high-strength carbonaceous products for the metallurgical industry.

[0010] Another technical effect of the present invention is to reduce the impact of coal tar production on the environment by replacing coal tar with petroleum sintering aids when releasing carcinogens.

[0011] Another technical effect of the present invention is to effectively utilize residual products from the hydrocracking of heavy oil feedstock in the production of a sintering aid composition.

[0012] By means of the sintering aid composition according to the invention, the technical problem is solved and the technical result is achieved.

[0013] According to the present invention, a sintering aid composition for manufacturing carbonaceous products is proposed, wherein the composition is composed of a concentrated residue from slurry phase hydrocracking of a heavy oil feedstock, and the aromatic hydrocarbon content is in the range of 23wt.% to 27wt.%, wherein the sintering aid composition is characterized in that, within the temperature range of 30°C to 850°C, the total weight loss is 50wt.% to 51wt.%, wherein the weight loss within the temperature range of 290°C to 570°C is about 95wt.% of the total weight loss.

[0014] Preferably, the content of carbene and oil coke in the composition is less than 20 wt.%, preferably less than 10 wt.%.

[0015] Preferably, the asphaltene content of the composition is about 33 wt.% to about 37 wt.%.

[0016] Preferably, the composition comprises at least 10 wt.%, preferably at least 20 wt.%, of polymerized petroleum resin.

[0017] Preferably, the composition is characterized by comprising 4 wt.% to 9 wt.% of mechanical impurities relative to the total weight of the composition.

[0018] The ash level of the composition is less than 1 wt.%, preferably between 0.4 wt.% and 0.6 wt.%.

[0019] Preferably, the sulfur content in the composition is less than 2.5 wt.%, preferably between 1.4 wt.% and 1.7 wt.%.

[0020] Preferably, the heavy oil feedstock used to make the composition is tar.

[0021] Preferably, the composition is obtained by a slurry phase hydrocracking technique, the unconverted residue of which is a slurry of porous coal additives in unconverted hydrocarbons in a liquid phase, the latter being the solid phase of said slurry.

[0022] Preferably, the concentrated residue from slurry phase hydrocracking is an unconverted residue from slurry phase hydrocracking which has been subjected to the steps of mixing with a solvent, separation from the solid phase, vacuum distillation of the solvent and concentration.

[0023] Preferably, the solid phase is separated from the liquid phase by centrifugal force.

[0024] Preferably, the solvent is an aromatic solvent, more preferably catalytically cracked aromatic gasoline.

[0025] Preferably, the concentrated hydrocracking residue is obtained by evaporating said unconverted residue free of solid phase and solvent, more preferably by vacuum evaporation from a thin film.

[0026] Preferably, the coal additive is characterized by a Barrett-Joyner-Halenda (BJH) mesopore volume of at least 0.07 cm 3 / g and less than 0.2cm 3 According to the present application, mesopores shall be considered to include pores having a diameter between 10 nm and 200 nm, more preferably between 20 nm and 50 nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 An overlay of three parallel thermal curves of the CRHT sample is shown.

[0028] Figure 2 Thermal curves of CRHT samples (first set of parallels) are shown. TGA curves are represented by square markers, DTG curves are represented by triangle markers, and DTA curves are represented by circle markers.

[0029] Figure 3 Thermal curves of CRHT samples (second set of parallels) are shown. TGA curves are represented by square markers, DTG curves are represented by triangle markers, and DTA curves are represented by circle markers.

[0030] Figure 4 Thermal curves of the CRHT samples (third set of parallels) are shown. The TGA curves are represented by square marks, the DTG curves are represented by triangle marks, and the DTA curves are represented by circle marks.

[0031] Figure 5 An overlay of thermal curves for 3 iterations of the CTP sample is shown.

[0032] Figure 6 Thermal curves of CTP samples (first set of parallels) are shown. TGA curves are represented by square markers, DTG curves are represented by triangle markers, and DTA curves are represented by circle markers.

[0033] Figure 7 Thermal curves of CTP samples (second set of parallels) are shown. TGA curves are represented by square markers, DTG curves are represented by triangle markers, and DTA curves are represented by circle markers.

[0034] Figure 8 Thermal curves of CTP samples (third set of parallels) are shown. TGA curves are represented by square marks, DTG curves are represented by triangle marks, and DTA curves are represented by circle marks.

[0035] Fig. 9The TGA curve, DTG curve, and DTA curve of the CRHT sample and the CTP sample are shown: the TGA curve is represented by square marks, the DTG curve is represented by triangle marks, and the DTA curve is represented by circle marks.

[0036] Fig.10 The infrared transmission spectra of the CRHT sample in 3 iterations are shown: the curve with circle marks represents the first iteration, the curve with triangle marks represents the second iteration, and the curve with square marks represents the third iteration.

[0037] Fig.11 The infrared transmission spectrum of the CTP sample is shown.

[0038] Fig.12 The results of comparing the infrared spectrum of the CRHT sample (curve with square marks) with the IR spectrum in the spectral database (curve with circle marks) are shown.

[0039] Fig.13 The infrared spectrum of the CRHT sample (curve with square marks) and the infrared spectrum of the CTP sample (curve with circle marks) are shown. DETAILED DESCRIPTION

[0040] The composition according to the invention comprises a concentrated residue from the slurry phase hydrocracking of a heavy oil feedstock.

[0041] The heavy oil feedstock is preferably tar. However, the raw material for hydrocracking may also be other high viscosity feedstocks, such as fuel oil, heavy gasoline, and the like.

[0042] In the present invention, slurry phase hydrocracking is liquid phase hydrocracking, and the unconverted residue is a slurry of waste coal additives (solid phase) in a liquid phase of unconverted high boiling hydrocarbons.

[0043] The hydrocracking residue is the unconverted residue which has been subjected to a purification step from the solid phase.

[0044] The purification step includes mixing the slurry with an aromatic solvent, separating the solvent-diluted liquid phase from the solid phase by, for example, centrifugal force, and removing the solvent from the mixture of solvent and unconverted residue.

[0045] The coal additive is characterized by a Barrett-Joyner-Halenda (BJH) mesopore volume of at least 0.07 cm 3 / g and less than 0.2cm 3 In the present invention, mesopores should be considered to include pores with a diameter between 10 nm and 200 nm, preferably between 20 nm and 50 nm.

[0046] Concentrated hydrocracking residues are residues from slurry phase hydrocracking which have been subjected to a concentration step, in particular thin film evaporation.

[0047] The advantage of the hydrocracking process for the production of sintering aids is that the sulfur contained in the oil feedstock reacts with hydrogen to produce hydrogen sulfide, which escapes later with the gaseous hydrocracking products. As a result, the sulfur content of the unconverted hydrocracking residue is reduced, which is crucial for the properties of the carbonaceous products further manufactured from the sintering aid. An important issue in the manufacture of coke or carbon electrodes is their CO 2 The presence of sulfur increases the reactivity of such products.

[0048] In the production of sintered carbonaceous products which must have high mechanical strength, high demands are placed on the composition of the charge components.

[0049] The inventors have found that the concentrated residue from slurry phase hydrocracking according to the invention has a high aromatic content, which is determined by its preparation method. More specifically, despite the presence of hydrogen, a condensation side process still occurs during the hydrocracking process due to the recombination of free radicals and carbocations. Aromatic hydrocarbons begin to participate in polycondensation reactions, so their molecular weight and boiling point increase accordingly, which determines the saturation of the residue with high boiling point resins (including aromatic resins).

[0050] Meanwhile, in addition to aromatic compounds, other high molecular weight compounds may exist in the hydrocracking residue, which are not desirable for sintering aids.

[0051] According to the present invention, slurry phase hydrocracking employs activated carbon, i.e., a porous coal additive in particulate form, having a high mesopore content. The fresh coal additive used in slurry phase hydrocracking in the present invention has a Barrett-Joyner-Halenda (BJH) mesopore volume of at least 0.07 cm 3 / g, preferably at least 0.12 cm 3 / g, even more preferably about 0.2 cm 3 / g. The diameter is between 10nm and 200nm, preferably between 20nm and 50nm, and the pores are related to mesopores. First and foremost, they increase the area of ​​the liquid-solid interface, and the hydroconversion process occurs at this liquid-solid interface. In the hydrocracking process, this is conducive to the active conversion of the asphaltenes present in the raw material into resins, mainly into high aromatic resins, to prevent them from condensing into carbenes and oil cokes, which are unwanted compounds in the sintering aid composition and can reduce the agglomeration ability of such additives. In addition, these carbenes and oil cokes already present in the raw material are adsorbed in the mesopores, and because the molecules of such compounds with a predetermined size (the molecules of the multilayer clustered structure penetrate the mesoporous material and settle in the holes), the mesopores can absorb these carbenes and oil cokes.

[0052] For these reasons, hydrocracking residues are characterized by a high content of aromatics and low contents of asphaltenes, carbenes and oil coke.

[0053] The unconverted residue from the slurry hydrocracking, including the waste coal additive, is then separated into a solid phase and a liquid phase. The liquid phase is a rather viscous liquid consisting of high-boiling hydrocarbons. The viscosity of the liquid phase must be reduced to separate the solid phase from the liquid phase. For this purpose, a solvent free of paraffins is used, preferably an aromatic solvent, which is a natural precipitant for asphaltenes. A preferred embodiment is a catalytically cracked aromatic gasoline. The unconverted residue is mixed with the solvent and separated by conventional techniques: precipitation, flotation, by centrifugal force. Separation by a cyclone separator is most preferred. The waste coal additive containing metals (including nickel and vanadium), asphaltenes, carbenes and oil coke is discharged from the unconverted residue, and the mixture of the hydrocracking residue and the solvent is evaporated in a vacuum tower, wherein the hydrocracking residue is substantially separated from the solvent and discharged as a vacuum bottom residue. Due to the thorough separation of the waste coal additive itself and the adsorbed components contained therein, which may increase the portion of incombustible residues, the ash level of the unconverted hydrocracking residue is reduced. Another advantage of removing the waste coal additive is that the sintering aid composition according to the present invention includes 4 wt.% to 9 wt.% of mechanical impurities relative to the total weight of the composition. The inventors have found that the amount of the mechanical impurities does not adversely affect the characteristics of the composition and the characteristics of the coke produced when the composition is used. Therefore, when the composition according to the present invention is used for blast furnace coke, the amount of the mechanical impurities will not cause clogging of the filter in the blast furnace when it is entrained in the blast furnace loaded with coke, and the calorific value of the blast furnace coke is still high. The amount of the above-mentioned mechanical impurities allows the production of products with appropriate strength. Without wishing to be bound by theory, the inventors believe that in areas where particulate mechanical impurities are present, when the sintering aid composition is used, a core of increased surface energy is generated, which may potentially be the starting point for cracking of the product. For these reasons, if the sintering aid composition contains a higher amount (more than 10 wt.%) of mechanical impurities, the mechanical strength / cracking resistance of the produced carbonaceous product may be reduced, and the ash level of the sintering aid is increased accordingly.

[0054] After separation of the waste coal additive, the purified residue from the slurry phase hydrocracking is further evaporated to remove the remaining light hydrocarbons and concentrate the fractions having an initial boiling point greater than 500°C. Therefore, more severe conditions are required: a higher vacuum and a higher temperature than in the vacuum tower in the previous step. Providing such conditions in a vacuum tower in the presence of a large amount of bottom residue will amplify the polycondensation reaction, that is, will increase coking. Therefore, thin film evaporation is mainly used because in a thin film under vacuum, evaporation proceeds faster at a lower temperature due to better heat distribution per unit area. The concentration process helps to accumulate fractions having an initial boiling point greater than 500°C, which, considering the previous process, are mainly high-boiling resins, including highly aromatic resins.

[0055] For the concentration, the residue of the tar hydrocracking is applied as a thin film to the inner surface of the thin film evaporator. Due to the increase in the total surface of evaporation under the influence of high temperatures of 420-480°C and due to the presence of a vacuum (at a residual pressure of -85 kPa to -99 kPa relative to atmospheric pressure), the residue is removed, the highly volatile components are removed, and the residue is concentrated without any risk of coking.

[0056] The bottom product from the evaporator is a concentrated hydrocracking residue, which can be used to make sintering aids for various by-products of the coking industry. Suitable products can be, for example, coke, more specifically metallurgical coke, foundry coke, in particular molded coke, wherein the sintering aid is used in the charge for the manufacture of suitable products. In addition, the sintering aid can be used as part of the charge for the manufacture of carbon electrodes such as anodes or cathodes for electroplating processes, in particular as part of the charge for the production of aluminum. The sintering aid can also be used as part of the charge for the preparation of self-sintered electrodes. The concentrated residue can also be further processed, for example in a delayed coking unit, for the manufacture of petroleum coke or anode coke.

[0057] The concentrated residue thus obtained is most suitable for use as a sintering aid for carbonaceous products for use in the metallurgical industry, having a low sulfur content of at most 2.5 wt.% and a low ash level of at most 1 wt.%.

[0058] In order to illustrate the possibilities of producing a sintering aid composition according to the invention, the following example of a method for its production is given below.

[0059] Example

[0060] A heavy oil raw material is mixed with 1.5 wt.% (based on the weight of tar) of two types of coal additives of different particle sizes. The heavy oil raw material is tar produced by removing lower boiling point fractions from Ural grade heavy oil, has an initial boiling point of 510°C, and a density of more than 1000 kg / m at 20°C. 3 , two particle sizes: a coarse fraction with a diameter of about 1 mm and a fine fraction with a diameter of about 0.3 mm. The coarse and fine fractions are characterized by different mesopore volumes: the fine fraction has a BJH mesopore volume of at least 0.07 cm 3 / g, while the BJH mesopore volume of the crude fraction is at least 0.12 cm 3 / g to more effectively adsorb asphaltene, the molecular size of asphaltene is 40nm to 90nm for tar produced from Urals crude oil. The BET specific surface area of ​​the coal additive is at least 230m 3 / g and less than 1230m 3 / g.

[0061] The feedstock in slurry form is sent to SPH (slurry-phase hydrocracking) where hydrogen is supplied at a temperature of 450°C and a pressure of 20 MPa. The mixture of coal additives, tar and gas passes through three SPH reactors, thereby producing a mixture of gaseous products and a slurry consisting of spent coal additives and unconverted high-boiling residues. The mixture is directed to a separation step, after which the gaseous stream is sent for gas-phase hydrocracking and the slurry is directed to an additive washing section consisting of a mixing tank and a cyclone separation tank.

[0062] The slurry from the unconverted high boiling residue is consumed at a rate of 15-20 tons / h together with the spent solid additives at a temperature of about 420°C and a pressure of less than 0.3 MPa and mixed in a mixing tank with a solvent, which is a catalytically cracked aromatic light gasoline, consumed at a rate of 30-35 tons / h at a temperature of about 220-260°C. In order to avoid excessive evaporation of the solvent, an overpressure of 0.15 MPa to 0.35 MPa is maintained in the mixing tank and is adjusted by a system of regulating valves.

[0063] The stream is then fed into a knockout drum equipped with a cyclone separator device where the spent additives are separated by centrifugal force from the unconverted high boiling residues in a mixture with catalytically cracked aromatic light gasoline.

[0064] After the washing stage, the waste coal additive is removed from the process, and the unconverted high-boiling residue in the mixture with the catalytically cracked aromatic light gasoline, which is heated to below 385°C, enters the vacuum tower. The vacuum pressure in the top of the vacuum tower is about 20 mm Hg, the pressure difference between the bottom of the vacuum tower and the lower packing bed (including the sealing disk) is about 7 mm Hg, and the temperature at the bottom of the vacuum tower is about 290°C.

[0065] The products produced during vacuum distillation are:

[0066] - light vacuum gas oil (LVG) and purified vacuum gas oil (PVG), and

[0067] - The separated heavy residue, ie the residual product from hydrocracking of tar (RPHT).

[0068] The separated heavy residue for concentration is fed to a thin-film evaporator (TFE) through a collector with discrete feed points.

[0069] The temperature in TFE was maintained at 400° C. The pressure in TFE was maintained at −95 kPa relative to atmospheric pressure (6.325 kPa under vacuum).

[0070] The film thickness was 1.12 mm and this thickness was constant along the height of the device.

[0071] The residence time of the above bottom residue in TFE for a predetermined film thickness is 20 seconds.

[0072] The concentrated residue of tar hydrocracking produced according to the proposed process has the characteristics listed in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] The softening point of the concentrated residue can be adjusted by changing the concentration process conditions (temperature, pressure, exposure time) in the thin film evaporator.

[0077] When the concentrated residue of the invention is used as a sintering aid, surprising results are obtained regarding the structure of the produced articles. Two types of molded coke samples were prepared from anthracite fines and a binder. As a binder, sample 1 included CTP (coal-tar pitch) and sample 2 included a sintering aid according to the invention. The sample based on CTP has a network of through cracks that reduce the strength characteristics of the article. At the same time, the sample based on the sintering aid is characterized by a dense, crack-free structure, while few and partial gas exit points (small channels) are observed.

[0078] On the one hand, due to the high content of aromatic compounds in the sintering aid composition, this structure is affected by good wettability, which ensures that the binder particles are firmly bonded. On the other hand, the sintering aid composition is characterized in that the volatiles are released most strongly when it is in the temperature range where the material is in a plastic state, for example, 290°C to 570°C. This is advantageous in several aspects. In particular, the gas escaping from the product forms small channels (ducts), which are quickly filled again by the material due to its plasticity, thereby providing a dense structure of the product without cavities, holes and cracks. Moreover, since most of the volatiles escape just when the sintering aid material is in a plastic state, the amount of gas released during the conversion of semi-coke to coke, that is, in the temperature range of 570°C or higher, is very small, so that the produced product shrinks slowly and evenly, and therefore, the cracks of the product are not large. The inventors have linked this phenomenon to the low content of carbenes and oil coke as coke precursors in the composition, which gives the composition more stable properties and a longer plastic period.

[0079] The sintering aid according to the invention comprises a large amount of high boiling point resins, including highly aromatic resins, which play an important role in wetting and impregnating the large amount of coal and its cementation when it further hardens. Due to the high wettability, the sintering aid establishes a strong bond between the particles. At this time, the gases escaping from the charge overcome a significant resistance, so that an opening is formed. In other cases, that is, in cases where the material has a low resistance to the escaping gases, the material breaks, which causes the product to crack and reduces its mechanical strength.

[0080] Comparative tests were carried out on samples of the concentrated residue of tar hydrocracking obtained according to the present invention and coal tar pitch.

[0081] 1. Thermogravimetric analysis (TGA)

[0082] The thermal behavior of samples of concentrated residue from tar hydrocracking (CRHT) and coal tar pitch (CTP) was studied on a synchronous thermal analyzer STA600 (Perkin Elmer). Thermogravimetric analysis (TGA) and differential thermogravimetry (TG-DTG) were used.

[0083] The investigated samples weighing about 25-30 mg were heated in a corundum crucible at a temperature range of 30°C to 850°C at a rate of 10°C / min. The analysis was performed in an inert gas (nitrogen) environment (gas supply rate 20 ml / min). Each sample was subjected to 3 replicates. The acquired data were processed by a special Pyris software utility. Figures 1 to 8 A graphical representation of the analytical results is shown in . The weight loss (TGA) data are listed in Table 2, with the maximum peak (DTG) indicated.

[0084] Table 2 – Thermal analysis results (nitrogen environment)

[0085]

[0086]

[0087] *(-) Maximum value of thermal transition not explicitly indicated.

[0088] Thermogravimetric analysis results of the CRHT sample in a nitrogen atmosphere showed that a slight weight loss of 0.06-0.07wt.% was observed on the TG curve in the low temperature range of 30-290°C. A major weight loss of 47.50-48.10wt.% was detected in the temperature range of 300°C to 570°C. The exothermic effect was observed to have several maxima at 465°C, 491°C and 497°C in this range on the TGA curve. As the temperature further increased to 850°C, a gradual loss of mass (2.9wt.%) was observed. In the high temperature range on the DTA curve, it was detected that the exothermic effect had a maximum at 626°C. The total weight loss under heating between 30°C and 850°C was 50.26-50.88wt.%.

[0089] A slight weight loss of 0.10-0.14 wt.% was detected on the TG curve of the CTP sample in the low temperature range of 30-160°C. The main weight loss of 54.89-55.03 wt.% was in the range of 160°C to 580°C. The DTA curve shows an endothermic effect in this range with a maximum at 507°C, which turns into an exothermic effect with an implicit maximum at 482°C and 504°C. As the temperature on the DTA curve increases, several exothermic effects are detected with a maximum at 556°C. The total weight loss of the CTP sample heated to 30-850°C is 56.94-57.02 wt.%.

[0090] Table 3 lists the weight losses of the CRHT samples and the CTP samples in the ranges of 370-430°C, 430-480°C, and 480-600°C.

[0091] Table 3 – Weight loss within specific ranges

[0092]

[0093] The results of thermogravimetric analysis show that the maximum weight loss of the CRHT sample is 47.50-48.10wt.% in the range of 300-570℃, and the maximum weight loss of the CTP sample is 54.89-55.03wt.% between 160-580℃. It is observed on the DTA curve of the CTP sample that the endothermic effect has a maximum value at 507℃, and the endothermic effect transforms into an exothermic effect at 482℃ and 504℃, with an implicit maximum value. In this range on the DTA curve of the CRHT sample, it is observed that the exothermic effect has several maxima at 465℃, 491℃ and 497℃. When heated to 30-850℃, the total weight loss of the CRHT sample is 50.26-50.88wt.%, while that of the CTP sample is 56.94-57.02wt.%. Fig. 9 The comparison curves of the CRHT sample and the CTP sample are shown in FIG.

[0094] 2. Fourier transform infrared spectroscopy

[0095] The CRHT and CTP samples were studied by Fourier transform infrared spectroscopy. The study was performed on a Frontier infrared Fourier transform spectrometer (Perkin Elmer) using an attenuated total reflectance (ATR) accessory. Figure 10-11 A graphical representation of the Fourier transform infrared spectroscopy results is shown in .

[0096] The infrared spectra of the studied samples contain a typical band (3038 cm -1 , 1601cm -1 ). At 700-900cm -1 There are also strong absorption bands in the 2921cm region, which may be evidence of the presence of monoalkyl-substituted aromatic compounds, dialkyl-substituted aromatic compounds, and trialkyl-substituted aromatic compounds in the sample. -1 and 1480cm -1 The absorption band at is CH 2 The characteristic of group vibration, 2852cm -1 and 1374cm -1 The band at is characteristic of methyl vibration.

[0097] The infrared spectra of the obtained CRHT samples are compared with the infrared spectra in the spectral database, Fig.12 The comparison results are shown in .

[0098] The infrared spectra of CRHT and CTP were also compared with each other ( Fig.13 ). Comparison shows that the infrared spectrum of the CPT sample is characterized by a smaller intensity of the absorption band.

[0099] 3. SARA Analysis

[0100] SARA Analysis Process

[0101] A portion of the CTP sample (same process for CRHT) is placed in a Soxhlet apparatus and extracted in a triple solvent mixture (toluene, chloroform, isopropanol); the process is continued until the solution becomes transparent. Then, the solvent mixture is distilled off using a rotary evaporator and n-hexane is poured in addition. The mixture is stirred and the flask is placed in a dark place overnight. The contents of the flask are filtered out through filter paper. The soft pitch enters the solution, while the asphaltenes, carbenes and tars remain on the filter paper, which is then placed in a Soxhlet apparatus. The extraction is stopped when the gradually decreasing solvent is completely decolorized. The contents of the receiving flask are distilled out using a rotary evaporator.

[0102] A glass chromatography column filled with a pre-calcined adsorbent (neutral alumina for chromatography) is used to separate the soft pitch. Before loading the sample of soft pitch, n-hexane is poured into the column to preliminarily wet the filler. Then, the soft pitch in the form of a n-hexane solution is loaded into the column. Thereafter, n-hexane, toluene, and a toluene / isopropanol mixture are poured into the column in the above order to elute saturated hydrocarbons, aromatic compounds, and resins, respectively. Each fraction is evaporated by a rotary evaporator and its content is determined.

[0103] The filter paper with asphaltenes, carbenes and oil coke in the Soxhlet extraction apparatus is extracted with toluene until the solvent is completely decolorized, the decolorized solvent is evaporated by a rotary evaporator, and the asphaltenes content is determined.

[0104] The same filter paper is then extracted with carbon disulfide in a Soxhlet apparatus until the clear solvent is reduced, then evaporated by a rotary evaporator and the asphaltenes content is determined. The amount of asphaltenes is determined from the residue on the filter paper.

[0105] Table 4 – SARA analysis of CTP

[0106]

[0107] Table 5 – SARA analysis of CRHT

[0108]

[0109] Results from the SARA analysis showed that when sintering aids were used, CRHT included an average of 10% more aromatics and almost 15 times more resins, which also play a key role in bonding.

[0110] Furthermore, SARA analysis showed that the content of poorly soluble high molecular weight hydrocarbons (e.g. carbenes and carbenes) was actually reduced by a factor of 5. These compounds have very low sintering and bonding functions, which again demonstrates the effectiveness of using CRHT as a sintering aid.

[0111] The analysis showed that CRHT has a higher aromatic content and a lower carbene and carbonaceous oil tar content than CTP, thus improving the wettability of the sintering aid of the present invention and prolonging its plasticizing period. The volatiles that escape during the sintering process after 480°C do not destroy the structure of the product to be sintered, which will cause cracking and form few and partially passed gas exit points.

Claims

1. A sintering aid composition for the manufacture of carbonaceous products, consisting of a concentrated residue of slurry phase hydrocracking of a heavy oil feedstock, wherein the aromatic hydrocarbon content is in the range of 23 wt.% to 27 wt.%, and the mechanical impurity content is 4 wt.% to 9 wt.% relative to the total weight of the composition.

2. The composition according to claim 1, wherein The content of carbene and oil coke is not more than 20 wt.%, preferably not more than 10 wt.%.

3. The composition according to claim 1, wherein The asphaltene content is 33 wt.% to 37.1 wt.%.

4. The composition according to claim 1, characterized in that It comprises at least 10 wt.%, preferably at least 20 wt.%, of a polymerized petroleum resin.

5. The composition according to claim 1, wherein The ash level is not more than 1 wt.%.

6. The composition according to claim 1, wherein The sulfur content is not more than 2.5 wt.%, preferably in the range of 1.4 wt.% to 1.7 wt.%.

7. The composition according to claim 1, wherein The composition is characterized in that within the temperature range of 30°C to 850°C, the total weight loss is 50 wt.% to 51 wt.%, wherein the weight loss within the temperature range of 290°C to 570°C is 94.0 wt.% to 96.0 wt.% of the total weight loss.

8. The composition according to claim 7, wherein The weight loss in the temperature range of 290° C. to 570° C. was 95 wt. % of the total weight loss.

9. A method for producing a sintering aid composition according to any one of claims 1 to 8, comprising the following steps: - subjecting a heavy oil feedstock to slurry phase hydrocracking, wherein the unconverted residue of the slurry phase hydrocracking is a slurry of a porous coal additive in unconverted hydrocarbons in a liquid phase, the porous coal additive being the solid phase of the slurry; - mixing the unconverted residue from slurry phase hydrocracking with a solvent; - separating the solid phase of the unconverted residue from the slurry phase hydrocracking from the mixture of liquid phase and solvent; - vacuum distilling the solvent from the liquid phase of the unconverted residue; - Concentrating the unconverted residue to produce a sintering aid composition.

10. The method according to claim 9, wherein: The heavy oil feedstock is tar.

11. The method according to claim 9, wherein: The solid phase is separated from the liquid phase by centrifugal force.

12. The method according to claim 9, wherein: The solvent is an aromatic solvent, preferably catalytically cracked aromatic gasoline.

13. The method according to claim 9, wherein: Concentration is carried out by evaporating the unconverted residue free of solid phase and solvent, preferably by vacuum evaporation from a thin film.

14. The method according to claim 9, wherein: The coal additive is characterized by a Barrett-Joyner-Halenda (BJH) mesopore volume of at least 0.07 cm 3 / g and not more than 0.2cm 3 / g.

15. The method according to claim 14, wherein: Mesopores include pores with a diameter between 10 nm and 200 nm, preferably between 20 nm and 50 nm.